Hubungan Antara Pola Asuh Orang Tua Dengan Perkembangan Moral Anak di Kelompok B TK Aisyiyah 1 Hadiluwih, Sragen. Tahun Ajaran 2016/2017 - Sari, Ira Nur Afifah, Drs. Haryono Yuwono,.SE.,M.Pd (2017)
Democratic parenting is a treatment for children with children's best interests at heart and open with each other between parents and their children. Pattern foster mutual respect democratic rights between parents and children. Parents set an example of mutual respect, giving clear rules and their consequences will be obtained, then the child will learn to know what you want and expect parents. Given these habits then the child will get used to the rules that exist in the society, therefore the child can control themselves, can be polite and respect each other. So with a comfortable upbringing among parents dang children then the moral child will be well ordered. The purpose of this study was to mengetaui relationship between parenting parents with the moral development of children in group B TK Aisyiyah 1 Hadiluwih Sragen. This study took place in kindergarten Aisyiyah 1 Hadiluwih 1 Sragen with this type of research is descriptive correlational. The population in this study were 45 children, and samples taken as many as 40 children in group B1 and B2, using random sampling techniques. Data parenting parents using questionnaires and moral development of the child obtained through a questionnaire. While data analysis technique using techniques Pearson product moment correlation analysis. Based on the correlation results in a significant level of 1% can be concluded that parents' parenting democratic had a significant relationship with the moral development of children, with a value r arithmetic amounted to 0.511 and the value r table amounted to 0,312, (r arithmetic > r table / 0.511> 0.312) with a significantly by 0.001 ( 0.001 <0.05). This means it can be seen that Ho refused and Ha accepted, meaning that there is a relationship between parents' parenting democratic with the moral development of children in kindergarten Aisyiyah 1 Hadiluwih Sragen Academic Year 2016/2017.